Conjunctural Trends in the Evolution of European and International Trade Legislation during the Post-Crisis Period - Sorin Mihai Stanciu (Scientific Papers Animal Science and Biotechnologies, 2023)
This paper aims at identifying the advantages and disadvantages of Romania in trade, in the context of profound structural changes in global and EU, on this basis, making recommendations and proposals for macroeconomic and microeconomic policy makers. Thus, on one hand, we have developed promotional policy proposals designed to support decision makers in our country, and on the other hand, proposals for business, so based on their Romanian exporters to eliminate weaknesses and to face the competition, both domestic and extra markets. Another major objective of the study was to formulate recommendations "of targeted" sectors with high export potential, given the directions for the period 2012-2016.